"We conquer or die" : Spanish Worker Appeal to you / by Julián Gorkin ; [introduction by Fenner Brockway] - Brockway, Fenner; Gorkin, Julián (1901-1987)
Precede al título: Two speeches which Sir John Simon tried to stop | Contiene: We fight fascism at the Front and build socialism behind. -- Unto the end : conquer or die